The Challenge of Implementing the Belt and Road Initiative in the Middle East: Connectivity Projects under Conditions of Limited Political Engagement. (10th January 2019) - Evron, Yoram
Abstract: Sceptics query China's economic and political ability to realize its Belt and Road Initiative (BRI). Less attention has been paid to BRI's implications for one of the defining features of China's foreign policy: low engagement in areas beyond its traditional sphere of influence. The Middle East is such a case. Addressing this issue, the article explores the mutual impact of China's low political involvement in the Middle East and BRI's realization. Distinguishing cross-border connectivity projects from other BRI-associated activities, the article examines the challenges to executing BRI-related projects in Israel. It finds that realizing connectivity projects – the essence of the BRI vision – will require China to increase its regional engagement, a shift that it has so far avoided. 摘要: 有批评人士质疑中国实现 "一带一路" 倡议的经济与政治实力。然而，鲜有人关注 "一带一路" 倡议对下述中国外交特征的影响，即中国外交对于其传统影响力之外的地区介入甚少。中东地区即属此例。针对这一现象，本文将着力探讨中国对中东事务的有限参与和实现 "一带一路" 倡议之间的相互影响。作者在区分跨境 "互联互通" 项目和其他 "一带一路" 相关项目基础上，分析在以色列推进 "一带一路" 有关项目将会面临的挑战。作者认为，要想实现作为 "一带一路" 愿景核心的 "互联互通" 工程，未来中国需要更多地参与中东事务。不过，迄今为止中国仍在避免调整其传统中东外交政策。